Health Data Privacy and GDPR Compliance in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The convergence of digital technology and healthcare has ushered in the era of Digital Health, promising unprecedented advancements in patient care and perso...
Keywords: Digital Health; Healthcare Innovation; Medical Ethics; Patient Care; Precision Medicine